MENINGKATKAN YOUNG ENTERPRENERSHIP DAN CREATIVE ENTERPRENERSHIP DI SMKN 2 SUMBAWA BESAR - Serli Oktapiani; Sri Andriani; Hartini; Putri Reno Kemala Sari; Muhammad Nur Fietroh (Mafaza : Jurnal Pengabdian Masyarakat, 2022)
Generation Z has a high interest in owning their own business (entrepreneurship). However, in many conditions, Generation Z lacks experience and knowledge of the concept of entrepreneurship. In providing solutions to these problems, community service activities are held for students who are still in school, especially for Vocational High School (SMK) students who will later become young entrepreneurs. In this service, students are given material on financial management, human resource management and also business strategy management. Using a workshop method filled by the Management Study Program service team, students are introduced to several important concepts in entrepreneurship, namely the role of human resource management, entrepreneurship strategies and the concept of financial planning. As a result of this workshop, students become more aware of and have an interest in entrepreneurship after graduating from secondary education.